Ultra-large-core single-mode fiber for optical communications: the segmented cladding fiber - Chiang, K.S.; Rastogi, V. (Optical Fiber Communications Conference: Post Conference Digest, 2002)
In conclusion, we have analyzed a 50 /spl mu/m-core segmented cladding fiber, which is capable of providing single-mode operation from 0.90 /spl mu/m to 1.70 /spl mu/m. We have elucidated the physical principle of the fiber with the radial effective index method whose accuracy has been confirmed with the finite-element method. The effective core area of the fiber is larger than those of any other large-core fiber designs by at least one or two orders of magnitude. We believe that we have opened up a new approach of designing ultra-large-core single-mode fibers for optical communications. The chromatic dispersion of the fiber and its control, as well as the bending loss and other practical issues are being studied.